Comunidade aprendente: a escola como locus de formação e desenvolvimento do professor - Ana Maria Vellenich; Adriano Marcius Ferreira; Nilsen Aparecida Vieira Marcondes; Maria Aparecida Campos Diniz de Castro (EccoS – Revista Científica)
There are peaceful opinions regarding the important role that education and training in school have a nation. However, in Brazil, for many years, school education has been facing different problems directly affects its quality. In this direction, this critical review of the literature proposes a ref lection on the educational institution as a system of relations, with obvious interactive features. The concepts and ideas of some authors studied this theoretical evidence the possibility of teacher training through shares present at the school. We conclude that ref lective practice and strategies for action, if carried out properly, turn the school into a learning community, which may contribute to the professional development and autonomy of the agents involved, as well as possible changes at the institutional level.